(untitled) (Journal of Asian Development Studies, 2024)
The crucial question regarding English language teaching (ELT) and learning is: does overuse of AI or other technology become an attack on the educational process in disguise? This study intends to explain the excessive use of AI in education and its upcoming negative aspects on ELT teachers’ identity and students’ creativity. The researchers used qualitative phenomenology to investigate how ELT teachers perceived AI’s impact on their leadership roles within the educational setting. As part of the research design, semi-structured interviews were conducted with sixteen ELT teachers and students from different districts in Punjab to obtain rich and detailed descriptions of their experiences and points of view using a purposive sampling technique. Under research question no.1 (Why does it seem that AI can be dangerous for ELT teachers’ identity in the future?), this study finds that AI can be hazardous for ELT teachers’ identity because it has shifted teachers’ roles from knowledge providers to facilitators only. In light of the second research question (what is the influence of AI on students’ self-motivation for creativity?), the significant finding is that AI negatively impacts students’ thinking abilities, and their creative skills diminish gradually. The study suggests that educational institutions must take drastic measures to address teachers’ apprehensions, misperceptions, and identity issues and clarify their roles and responsibilities in AI-driven educational scenarios where they may continue promoting creativity in the students under their charge.